THE INFLUENCE OF THE EXTERNAL ENVIRONMENT ON THE BIOLOGICAL AND TECHNOLOGICAL PROPERTIES OF COCOONS (Ideal Journal of Multidisciplinary Research, 2026)
In addition to heredity, the biological and especially technological properties of cocoons are greatly influenced by the conditions of cocoon wrapping - temperature, humidity, light, ventilation (aeration), the quantity and quality of cocoons.As a result of temperature changes during cocoon wrapping, the speed and nature of the silkworm wrapping the silk fibers into the cocoon shell of the worm also change.
Keywords: Cocoon, cocoon, temperature, humidity, varietal cocoons, spotted cocoons, biological indicators, mulberry leaves, high productivity, preserved live cocoons, cocoon production, live cocoon, productivity, varietal cocoons, technological indicators.